Childhood invasive bacterial disease in Kathmandu, Nepal (2005-2013) - Carter, MJ; Gurung, M; Pokhrel, B; Bijukchhe, SM; Karmacharya, S; Khadka, B; Maharjan, A; Bhattarai, S; Shrestha, S; Khadka, B; Khulal, A; Gurung, S; et al. (Lippincott, Williams and Wilkins, 2021)
Background: Invasive bacterial disease (IBD; including pneumonia, meningitis, sepsis) is a major cause of morbidity and mortality in children in low-income countries.